KETERKAITAN PEMODELAN MATEMATIS DALAM PENYELESAIAN SOAL CERITA - Lasmika Veronika Pandiangan; Rafiq Zulkarnaen (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to identify the stages of mathematical modeling carried out by students in solving story problems. Case studies with single cases and single analyses were used in this research. The research subjects used in this study were 4 students of class VII at a State Junior High School in Karawang Regency, West Java Province. The research subjects were selected using the purposive sampling technique. The test instrument and non-instrument used in this study, the test instrument in the form of a story on the material of linear equations, and the non-test instrument were unstructured interviews. The results of the study concluded that the stages of mathematical modeling carried out by students in solving story questions, mathematics was used in the process of problem representation and solution execution, while dematematization was used in the interpretation of story problem-solving.